Blood Pressure Nomograms for Children and Adolescents by Age and Body Mass Index in Tehran, Iran - Neamatollah ATAEI; Masoud BAIKPOUR; Mostafa HOSSEINI; Mahmoud YOUSEFIFARD; Mohammad FAYAZ; Fatemeh ATAEI; Arash ABBASI (Tehran University of Medical Sciences, 2017)
Background: Normal standard references of blood pressure (BP) for children and adolescents should be constructed according to anthropometric indices. Therefore, we aimed to produce BP reference percentiles by body mass index (BMI). Methods: Data on demographic characteristics, anthropometric indices and BP values of 16246 3-18-year-old children and adolescents from 3 cross-sectional studies conducted in Tehran were included. To justify the need for BMI adjustment, quantile regression model was applied for different percentiles of systolic and diastolic BPs with age, sex, and the corresponding BMI percentiles. Then, Age- and sex-specific BP nomograms were constructed according to BMI. Results: All regression coefficients for BMI percentiles were significant in quantile regression of BPs, confirming the necessity for BMI-adjusted nomograms of BP. The BP percentiles for each gender by age and BMI are presented. All the BP percentiles rose steadily in all BMI percentiles with minor discrepancies between the two genders. As observed, the prevalence of hypertension is estimated to be lower among the lean subjects and higher among overweighs when the BMI-adjusted BP curves are considered. Conclusion: The reference database constructed in this survey is the first Iranian BP reference by age and BMI in children and adolescents, from it concluded that BMI-adjusted BP curves depict a more precise picture of the hypertension prevalence and present a more reliable classification standard for hypertension.